Odpowiedź :
a)
3(2x + 1) + 5x = 2(3x + 2) - 11
6x + 3 + 5x = 6x + 4 - 11
11x + 3 = 6x - 7
11x - 6x = -7 - 3
5x = -10 / : 5
x = -2
b)
6(1 - x) + 2(x + 1) = 10 - 5x
6 - 6x + 2x + 2 = 10 - 5x
-4x + 8 = 10 - 5x
-4x + 5x = 10 - 8
x = 2
[tex]3\ (2x + 1) + 5x = 2\ (3x + 2) - 11[/tex]
[tex]6x + 3 + 5x = 6x + 4 - 11[/tex]
[tex]6x + 5x - 6x = 4 - 11 - 3[/tex]
[tex]5x = -10\ |: 5[/tex]
[tex]\boxed{x = -2}[/tex]
[tex]6\ (1 - x) + 2\ (x + 1) = 10 - 5x[/tex]
[tex]6 - 6x +2x + 2 = 10 - 5x[/tex]
[tex]-6x + 2x + 5x = 10 - 6 - 2[/tex]
[tex]\boxed {x = 2}[/tex]